Reverse‐Engineered Highly Conformable, Leak and Pressure Reducing Cushion for Neonatal Resuscitation Mask. Issue 7 (30th December 2021) - McGann, Carolyn M.; Lee, Young‐Joo; Kim, Se‐Um; Weinberg, Danielle D.; Zha, Xincheng; Huber, Matthew; Hast, Michael W.; Dear, Kayley; Nadkarni, Vinay; Foglia, Elizabeth E.; Yang, Shu
Abstract: A significant proportion of newborn infants need facemask assisted resuscitation to start breathing successfully after birth. Positive pressure ventilation (PPV) is the most important intervention yet often impeded by facemask leak. A conformable, tacky silica gel that can be attached to the mask as a cushion is developed through reverse engineering. Finite element simulation reveals that the cushion forms a completely sealed interface while the mask alone without cushion has many potential leak sites. Since the cushion material is 20 times softer than the facial tissue, most deformation occurs in the cushion when applied, resulting in a fivefold lower contact pressure than using a conventional mask only. In a simulation trial with a realistic preterm manikin, the median mask leak for PPV inflations using the cushion is 15%, three times lower compared to that using the conventional mask alone, 44%. The median time to achieve leak‐free is 16 s with the mask cushion, five times faster than that with standard mask, 81 s, allowing for more effective ventilation. This study offers promising insights on how the design of a 3D‐contoured, soft silicone gel as the interface between a mask and a face can significantly improve neonatal resuscitation performance. Abstract : A 3D‐contoured cushion made of soft silicone that is 20 times softer than the facial tissue is reverse‐engineered to improve the conformability of a commercial neonatal resuscitation mask on face, allowing for more effective ventilation. It is shown the cushion can form a completely sealed interface and thus reduce mask leak while maintaining lower contact pressure on the face.